2022
DOI: 10.1029/2022jf006783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bed Hydrophobicity on Post‐Fire Debris Flow Entrainment and Momentum Growth

Abstract: Forest wildfires leave vast areas with burned topsoil that is water repellent, susceptible to erosion by surface runoff and a potential source of debris flow. To mitigate post‐fire debris flow hazards, debris resisting barriers are usually constructed in the flow path. However, the fundamental interaction mechanisms of debris flow on a water repellent bed and the momentum exchange process that governs the destructive potential of debris flows have yet to be elucidated. This study investigates the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
(197 reference statements)
0
6
0
Order By: Relevance
“…Rengers et al (2021), also working in the San Gabriel Mountains, used airborne and terrestrial lidar to determine that only 7% of postfire sediment erosion originated from channels, whereas 93% was derived from hillslopes; postfire erosion rates were of the same magnitude as millennial-scale bedrock erosion rates, suggesting that fires account for a majority of longterm erosion in that region. Flume experiments by Ng et al (2022) investigated the effects of soil hydrophobicity (water repellency) on debris-flow entrainment and momentum growth. Their study demonstrated unique erosion patterns and showed that the erosion depth of a debris flow can be six times greater when occurring in a hydrophobic bed similar to one that would be present after a wildfire.…”
Section: Postfire Landscape Processes and Physical Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rengers et al (2021), also working in the San Gabriel Mountains, used airborne and terrestrial lidar to determine that only 7% of postfire sediment erosion originated from channels, whereas 93% was derived from hillslopes; postfire erosion rates were of the same magnitude as millennial-scale bedrock erosion rates, suggesting that fires account for a majority of longterm erosion in that region. Flume experiments by Ng et al (2022) investigated the effects of soil hydrophobicity (water repellency) on debris-flow entrainment and momentum growth. Their study demonstrated unique erosion patterns and showed that the erosion depth of a debris flow can be six times greater when occurring in a hydrophobic bed similar to one that would be present after a wildfire.…”
Section: Postfire Landscape Processes and Physical Hazardsmentioning
confidence: 99%
“…Flume experiments by Ng et al. (2022) investigated the effects of soil hydrophobicity (water repellency) on debris‐flow entrainment and momentum growth. Their study demonstrated unique erosion patterns and showed that the erosion depth of a debris flow can be six times greater when occurring in a hydrophobic bed similar to one that would be present after a wildfire.…”
Section: Postfire Landscape Processes and Physical Hazardsmentioning
confidence: 99%
“…Existing literature (McCoy et al., 2012; McGuire et al., 2017; Ng et al., 2022; Wilcock & McArdell, 1993; Winterwerp et al., 2012) demonstrates that progressive scouring and mass failure are two main mechanisms by which a soil bed is eroded. Scouring occurs when a soil bed is eroded at its surface grain‐by‐grain by hydrodynamic shear stress (Fraccarollo & Capart, 2002; Shields, 1936).…”
Section: Introductionmentioning
confidence: 99%
“…Mass failure occurs when a soil bed fails en masse as a block along a failure plane (Ng et al., 2022; Takahashi, 1978). Takahashi (1978) proposed that mass failure of a soil bed is prone to occur in loose saturated soils, where soil is liquefiable under the influence of external loading imposed by a debris flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation